Peranan Digital Marketing Sebagai Strategi Pemasaran Secara Online Bagi Usaha Mikro, Kecil, Dan Menengah (UMKM) Berdasarkan Syariah Islam Di Desa Teluk Pinang Kecamatan Ciawi - Egi Setiadi; Kholifatul Husna Asri (Neolectura, 2023)
Digital marketing is a combination of all marketing activities carried out through electronic media and the internet. Some of the digital marketing activities include SEO, SEM, social media marketing, email marketing, content marketing and more. Facebook Instagram with the advent of the Internet in the 1990s, digital marketing has become widespread on the internet through marketplaces or social networks such as Facebook, Tiktok and Instagram. The purpose of this study is to explain the impact of digital marketing and digital marketing expertise, especially with social media access, to increase sales and profits for small and medium enterprises (MSMEs) in Telukpinang Village. The research approach used consisted of a qualitative method using a triangulation model that combined in-depth interviews and observations with the chairman of the Teluk Pinang village MSME Forum, Bunda Wilis Sugiarti, and several MSME stakeholders in the forum discussing the economic situation of MSME stakeholders after the COVID-19 pandemic and several MSME marketing strategies in Teluk Pinang village: based on the results of the study, one of the challenges experienced by some MSME business actors is Product Marketing. After the implementation of extensive social restrictions (PSBB) and community activity restrictions (PPKM) in 2021 is still ongoing, agents are trying various ways to market their products to keep their business running. Therefore, these MSMEs need to be educated about the importance of using digital marketing to improve their marketing system. Thus, MSMEs can expand the scope of their business objectives and show better sales activity. Digital marketing makes it easy for MSME players to provide information, interact directly with consumers, increase understanding of digital marketing strategies, and increase MSME awareness.